Description of Patient Knowledge and Compliance, Implementation and Completeness of Discharge Planning Documentation in the Hemodialysis Room of the Hospital - Diah Priyantini; Daviq Ayatulloh; Nursalam Nursalam (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2026)
Background: The rate of non-compliance among hemodialysis patients, particularly with regard to fluid intake and dietary restrictions, remains very high, ranging from 30–81.4%. This study aimed to assess patient knowledge and compliance, while also reviewing the implementation and completeness of discharge planning documentation in hospital hemodialysis wards. Methods: This study used a descriptive correlational design with a cross-sectional approach, conducted from July 15–30, 2021, at Haji Hospital Surabaya and Muhammadiyah Hospital Lamongan. The participant criteria were patients with chronic kidney disease undergoing hemodialysis for more than three months, aged 21 years and over, able to read and write, familiar with internet usage, and able to operate Android-based applications. The total sample size was 105 individuals selected using simple random sampling. Patient compliance was evaluated using the End-Stage Renal Disease Adherence Questionnaire (ESRD-AQ), knowledge was assessed using the Kidney Disease Questionnaire, and the completeness of nurses' discharge planning was measured using the IDEAL Discharge Planning Checklist. Data analysis was performed using descriptive statistics using frequency distributions. Results: Respondents were mostly male (49.1%), aged 46–55 years (49.1%), married (87.3%), and still employed (59.9%). Patients' knowledge of fluid restriction was moderate to good, while adherence to fluid restriction was only adequate. The highest level of non-adherence was found in the fluid and diet aspects. The results of the discharge planning assessment showed that implementation and completeness of documentation were still adequate. Conclusion: The level of knowledge and adherence of patients with chronic kidney disease are closely related to the quality of discharge planning implementation carried out by nurses.